Pengaruh Keterlibatan Kerja, Motivasi Kerja, Budaya Organisasi dan Disiplin Kerja Terhadap Kepuasan Kerja - Fajrin Mubarokh (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2024)
This study aims to analyze the effect of work engagement, work motivation, organizational culture and work discipline on employee job satisfaction. The type of research used is quantitative methods with descriptive analysis. The data collection technique was carried out online with a questionnaire using a Likert scale of one to five and obtained by a simple random sampling method on 126 respondents with criteria over the age of 18 years and had worked or were working. The data analysis techniques used in this study are: Outer Model with Convergent Reliability, Composite Reliability, Cronbach's Alpha and Inner Model calculations with T statistic, R-Square, f-Square, and VIF calculations using SmartPLS (Partial Least Square) tools version 4.0.9.3. The results showed that: 1) Work involvement has a significant influence on employee job satisfaction. 2) Work motivation has a significant influence on employee job satisfaction. 3) Organizational culture has a significant influence on employee job satisfaction. 4) Work discipline has a significant influence on employee job satisfaction.